Analysis of aerodynamic characteristics of a two-bladed wind power plant containing combined power elements - А.Ж. Тлеубергенова; А.Н. Дюсембаева; Н.К. Танашева; Ш.С. Кыздарбекова; А.Р. Мухамедрахим (Қарағанды университетінің хабаршысы. Физика сериясы)
In this article, the aerodynamic characteristics of a wind turbine of various parameters are studied. For this purpose, an experimental two-cylinder model with fixed blades was made. A schematic diagram of a wind turbine with fixed blades and rotating cylinders is obtained. The airflow velocity varied from 3 to 12 m/s. The dependences of the aerodynamic forces of a wind power plant on the flow velocity were investigated. The analysis of the results of the experiment on changing the angle α of the fixed blade relative to the cylinder from the airflow velocity of the wind turbine is carried out. When the position of the blade changes, the drag changes relative to the airflow. A graph is constructed based on the dependence of drag and lift forces on the flow velocity. It is established that at the maximum angle relative to the cylinder α = 30° that the value of the lifting force and the drag force of the fixed blade is higher. From the dependence of the coefficient of lift and drag force on the Reynolds number, it was found that at an angle of 30° degrees, there is a minimum lifting force of 0.04 and a maximum drag force of 1.479 at Re=1·104. The results of the experiment show that it is possible to use an additional force driven by the Magnus effect that occurs when rotating cylinders with a horizontal axis. These results are considered useful for us in practice since these results can be used in combined wind engines operating at low wind speeds. This wind power plant can generate electricity starting from a wind speed of 2.8 m/s.